13C-Mixed Triglyceride Breath Test and Fecal Elastase as an Indirect Pancreatic Function Test in Cystic Fibrosis Infants. Issue 5 (May 2018) - Kent, Dorothea Stark; Remer, Thomas; Blumenthal, Caron; Hunt, Sharon; Simonds, Sharon; Egert, Sarah; Gaskin, Kevin J.
ABSTRACT: Background: The 'gold standard' test for the indirect determination of pancreatic function status in infants with cystic fibrosis (CF), the 72-hour fecal fat excretion test, is likely to become obsolete in the near future. Alternative indirect pancreatic function tests with sufficient sensitivity and specificity to determine pancreatic phenotype need further evaluation in CF infants. Objective: Evaluation of the clinical utility of both the noninvasive, nonradioactive 13 C-mixed triglyceride (MTG) breath test and fecal elastase-1 (FE1) in comparison with the 72-hour fecal fat assessment in infants with CF. Methods: 13 C-MTG breath test and the monoclonal and polyclonal FE1 assessment in stool was compared with the 72-hour fecal fat assessment in 24 infants with CF. Oral pancreatic enzyme substitution (PERT; if already commenced) was stopped before the tests. Results: Sensitivity rates between 82% and 100% for CF patients with pancreatic insufficiency assessed by both the 13 C-MTG breath test and the FE1 tests proved to be high and promising. The 13 C-MTG breath test (31%–38%) as well as both FE1 tests assessed by the monoclonal (46%–54%) and the polyclonal (45%) ELISA kits, however, showed unacceptably low-sensitivity rates for the detection of pancreatic-sufficient CF patients in the present study. Conclusions: The 13 C-MTG breath test with nondispersive infrared spectroscopy (NDIRS) technique, as well as both FE1 tests, are not alternatives to the fecal fat balance test for the evaluation of pancreatic function in CF infants during the first year of life. Abstract : Supplemental Digital Content is available in the text